Expression of SERK family receptor-like protein kinase genes in rice - Ito, Y.; Takaya, K.; Kurata, N.
Some SERK-family receptor-like protein kinase genes have been shown to confer embryonic competence to cells. In this study, we isolated two novel rice genes, OsSERK1 and OsSERK2, belonging to the SERK-family. OsSERK2 showed constitutive expression. The OsSERK1 promoter showed reporter gene activities in some specific tissues in a germinating seed, leaf and root, but not in a developing embryo. This promoter activity suggests that OsSERK1 may have roles in non-embryonic tissues rather than in the embryo.
Keywords: SERK; RECEPTOR-LIKE PROTEIN KINASE; EMBRYOGENESIS; GENE EXPRESSION; RICE